Analysis of Current Harmonics Compensation and the Effect of Frequency Variation for Single-Phase Stand-Alone PV Inverters using PR Controller - Akter, Md Parvez; Elias, Mohamad Fathi Mohamad; Rahim, Nasrudin Abd (Taylor & Francis, 2018)
This paper presents the analysis of current harmonics compensation using the proportional-resonant controller for single-phase stand-alone photovoltaic inverter applications. The effect of frequency variation in the reference signal to the controller performance was also analyzed. The controller parameters (K p , K i , and ω c ) and the inductor-capacitor (LC)-filter parameters are optimally selected to obtain a very low current total harmonic distortion. The control algorithm was implemented using a low-cost digital signal processor (DSP) TMS320F28335 eZdsp development board. Both simulation and experimental results validate the performance and the effectiveness of the control technique used.